1998
DOI: 10.1111/1468-5876.00093
|View full text |Cite
|
Sign up to set email alerts
|

Land-Tax, Transfer and Growth in an Endogenously Growing Economy with Overlapping Generations

Abstract: In this paper we investigate the effect of a tax on land rent on the growth rate of capital in a growing economy with overlapping generations. A tax on land rent has a potential to increase the growth rate of capital. If the model is extended to allow the tax revenue to be refunded to individuals, a tax on land rent may deter growth to the extent that the tax revenue is transferred to the older generation. JEL Classi®cation numbers: H31, O41.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Further, Stauvermann (2002) showed that the result still holds if land is not traded but inherited from generation to generation. This outcome is consistent with the study of Hashimoto and Sakuragawa (1998) in which the land tax revenue is transferred to the old generation in a lump-sum fashion. The argument in both papers is that the willingness to save declines if the individuals receive additional income or wealth in the second period of life.…”
Section: Literature Review: Land Taxationsupporting
confidence: 90%
See 2 more Smart Citations
“…Further, Stauvermann (2002) showed that the result still holds if land is not traded but inherited from generation to generation. This outcome is consistent with the study of Hashimoto and Sakuragawa (1998) in which the land tax revenue is transferred to the old generation in a lump-sum fashion. The argument in both papers is that the willingness to save declines if the individuals receive additional income or wealth in the second period of life.…”
Section: Literature Review: Land Taxationsupporting
confidence: 90%
“…In what follows, we analyze if the main insights and results gained by others (c.f. Tirole 1985;Homburg 1991;Fane 1984;Chamley and Wright 1987;Grossman and Yanagawa 1993;Hashimoto and Sakuragawa 1998;Stauvermann 2002;Koethenbuerger and Poutvaara 2009;Edenhofer et al 2015;Dao and Edenhofer 2018) can be confirmed. The novelty of the paper is that it is the first study to consider, in an overlapping generations (OLG) framework, the possibility of using land for production purposes or housing purposes and the subsequent effect of different land taxes and the redistribution of the respective tax revenue to the young generation on economic growth.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In all the cases studied by Ihori (1990), the nominal price of land is normally reduced by land taxes, while the real price may rise or fall. Hashimoto and Sakuragawa (1998) found in a "learning by doing" endogenous growth economy with finite horizons that the effects of the imposition of a land tax differ according to the tax-transfer programme adopted. If the 3 The analysis of the land tax effects is only one of the several issues investigated by Eaton (1988) in an open economy with reproducible capital and unimproved land.…”
Section: Introductionmentioning
confidence: 99%
“…Petrucci as well as Koethenbuerger and Poutvaara state that a land rent tax leads to higher capital and consumption for the case originally considered by Feldstein, but model a small open economy with a fixed interest rate for their own analysis and do not consider the welfare effects and the redistribution possibilities of the land tax revenue. Hashimoto and Sakuragawa (1998) study a land rent tax in a discrete OLG model with endogenous technological change. They also find that it is preferable to redirect the revenue to the young generation as this increases the economic growth rate, but a Pareto improvement cannot be reached in their model, and social optimality is not analysed.…”
Section: Introductionmentioning
confidence: 99%